Detection of Norwalk virus and hepatitis A virus in shellfish tissues with the PCR. - Atmar, R L (1995)
A method for the detection of Norwalk virus and hepatitis A virus from shellfish tissues by PCR was developed. Virus was added to the stomach and hepatopancreatic tissues of oysters or hard-shell clams, and viral nucleic acids were purified by a modification of a previously described method (R.L. Atmar, T.G. Metcalf, F.H. Neill, and M.K. Estes, Appl. Environ. Microbiol. 59:631-635, 1993). The new method had the following advantages compared with the previously described method: (i) more rapid sample processing; (ii) increased test sensitivity; (iii) decreased sample-associated interference with reverse transcription-PCR; and (iv) use of chloroform-butanol in place of the chlorofluorocarbon trichlorotrifluoroethane. In addition, internal standards for both Norwalk virus and hepatitis A virus were made which demonstrated when inhibitors to reverse transcription-PCR were present and allowed quantitation of the viral nucleic acids present in samples. This assay can be used to investigate shellfish-associated gastroenteritis outbreaks and to study factors involved in virus persistence in shellfish.